A Methodological Study on Tuning the Thermally Activated Delayed Fluorescent Performance by Molecular Constitution in Acridine–Benzophenone Derivatives. Issue 9 (30th March 2018) - Yang, Rongjuan; Guan, Qian; Liu, Zhiyang; Song, Wei; Hong, Ling; Lei, Tao; Wei, Qiang; Peng, Ruixiang; Fan, Xi; Ge, Ziyi
Abstract: Thermally activated delayed fluorescent (TADF) emitters are usually designed as donor–acceptor structures with large dihedral angles, which tend to incur low fluorescent efficiency, and therefore, through molecular design various strategies have been proposed to increase the efficiency of emitters; however, few studies have compared these strategies in one TADF system. In this study, a novel TADF molecule, [4‐(9, 9‐diphenylacridin‐10‐yl)phenyl](phenyl)methanone (BP‐DPAC ), was designed as a prototype, and two derivatives, BP‐Ph‐DPAC andDPAC‐BP‐DPAC, were also prepared to represent two common approaches to enhance TADF performance. Compared with the maximum external quantum efficiency (EQE) of 6.82 % forBP‐DPAC, organic light‐emitting diodes (OLED) devices based onDPAC‐BP‐DPAC exhibited enhanced TADF properties with the highest maximum EQE of 18.67 %, owing to an additional diphenylacridine donor, whereasBP‐Ph‐DPAC showed non‐TADF properties and exhibited the lowest EQE of 4.25 %, owing to the insertion of a phenyl ring between donor and acceptor. Abstract : Differing donors : A prototype donor–acceptor (D‐A) molecule (see figure) was designed to study the thermally activated delayed fluorescent (TADF) properties of emitters in organic light‐emitting diodes. Structure variation revealed that the TADF properties could be enhanced by inserting an additional D into the molecule, whereas the insertion of a phenyl bridge between D and A led to a loss in TADF properties.